Zweisprachige Aufschriften in Kärnten - Vom Ortstafelsturm zur Konsenskonferenz - Kert-Wakounig, Sonja (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2010)
Bilingual topographical signs and the issue of a positive attitude towards the Slovenian language in the southern Austrian province of Carinthia have been the subjects of a longstanding public debate. Through interviews with 'ordinary' Carinthian Slovenes, people who are outside the public eye but who,nevertheless, are directly affected by the highly charged atmosphere of the language conflict within which their daily lives take place, this article will address the process of the transformation of language-related values in Carinthia within the community of Carinthian Slovenes from 1972 to the present. The author attempts to ascertain the importance of the symbolic merit of bilingual topographical signs in helping to preserve language and identity, while trying to assess whether a significant increase in the value of the Slovenian language amongst the broader population has occurred. It will also evaluate the role of the so-called Consensus Group for Carinthia in the processes involved.
Keywords: Koroška; avstrijska Koroška; Carinthia; Carinthian Slovenes; koroški Slovenci; krajevni napisi; dvojezični napisi; identiteta